THE INFLUENCE OF EDUCATION, HEALTH, POVERTY, AND UNEMPLOYMENT ON ECONOMIC GROWTH THROUGH THE HDI IN SOUTH SUMATERA 2017-2021: Drirect Iinfluence, Indirect influence - Hidayat, Randy; Sahri, Yulian (I-Economics, 2023)
Abstract Southern Sumatra consists of the provinces of South Sumatra, Lampung, Jambi, Bengkulu, and the Bangka-Belitung Islands. These five provinces have the fastest recovering economic growth compared to other regions in Indonesia and the highest economic growth recovery in Sumatra from 2020-2021. Therefore, this study aims to analyze what factors influence economic growth in 60 cities/districts in Southern Sumatra. Key Words: Factors, Economic Growth, Southern Sumatra